2020
DOI: 10.1080/1354750x.2020.1833084
|View full text |Cite
|
Sign up to set email alerts
|

Copeptin combined with either non-high sensitivity or high sensitivity cardiac troponin for instant rule-out of suspected non-ST segment elevation myocardial infarction

Abstract: Background: Whether Copeptin combined with high sensitivity troponin below the respective decision cut-offs improves rule-out of NSTEMI and may predict all-cause death at 30-day is under debate. Methods: Data on 10,329 patients from 5 trials were pooled to evaluate the diagnostic and prognostic performance of an initial Copeptin below decision cut-off in combination with a (hs)-cTn below the uppler limit of normal (ULN) compared to a) the initial (hs)-cTn alone in the standard serial sampling strategy based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…However, some studies have concluded that this dual marker strategy (combination of copeptin and hs-cTn) might provide higher eligibility or efficacy (quantified by the percentage of the overall cohort assigned to the rule-out zone) to rule out NSTEMI ( 89 , 102 , 103 ). Giannitsis et al evaluated pooled data of 10,329 patients and concluded that the NPV for ruling out NSTEMI was high for the dual marker strategy (copeptin < 10 pmol/L and/or hs-cTn ≤ 14 ng/L) and single marker strategy (hs-cTnT < 5 ng/L) to be 99.0 and 99.2%, respectively, but the former had a 2.4-fold higher eligibility [64.6% (63.0–66.2%) vs. 27.9% (26.2–29.7%)].…”
Section: Copeptin In Amimentioning
confidence: 99%
“…However, some studies have concluded that this dual marker strategy (combination of copeptin and hs-cTn) might provide higher eligibility or efficacy (quantified by the percentage of the overall cohort assigned to the rule-out zone) to rule out NSTEMI ( 89 , 102 , 103 ). Giannitsis et al evaluated pooled data of 10,329 patients and concluded that the NPV for ruling out NSTEMI was high for the dual marker strategy (copeptin < 10 pmol/L and/or hs-cTn ≤ 14 ng/L) and single marker strategy (hs-cTnT < 5 ng/L) to be 99.0 and 99.2%, respectively, but the former had a 2.4-fold higher eligibility [64.6% (63.0–66.2%) vs. 27.9% (26.2–29.7%)].…”
Section: Copeptin In Amimentioning
confidence: 99%
“…Therefore, the interpretation and communication of hs troponin test results require training and clear rules. In addition, other biomarkers like copeptin may help to solve this dilemma, which is supported by ample evidence [9–13]. The scientific noteworthiness of the ESC guidelines related to other biomarkers than troponin for the initial diagnosis of ACS has been outlined elsewhere in detail [14,15].…”
Section: Guideline Highlights For the Edmentioning
confidence: 99%
“…Furthermore and in line with previous studies, our results confirm that copeptin is efficient and safe in rule-out of AMI in combination with hs-cTn. 38 Finally, our study addresses the value of prehospital sampling for copeptin measurement and thus a potential for future prehospital rule-out if relevant POC equipment becomes available. The utilization of the prehospital phase for diagnostic activities contains great potential for optimizing the management of chest pain patients.…”
Section: Discussionmentioning
confidence: 99%